The evolution of posterior cervical fusion: A tribute to Frederick P. Dewar, M.D. and Edward. H. Simmons, M.D. - Morgan P. Lorio; Avi J. Bernstein; William N. Capicotto; Edward D. Simmons; Jon E. Block (World Neurosurgery: X)
This historical vignette is a tribute to Professors Frederick P. Dewar and Edward H. Simmons who were pioneers in the evolution of posterior cervical fusion. In response to failures of other wiring techniques, they developed a posterior cervical fusion construct based on sound biomechanical principles. The so-called “Dewar” technique utilized contoured double cortico-cancellous iliac grafts as internal graft-splints fixed to the spine with threaded pins and wire to enhance posterior cervical stability. This technique has since been replaced by lateral mass screw constructs and interfacet fusion techniques which facilitate midline decompression while maintaining stability. This paper provides an historical perspective on the Dewar technique, illustrating its impact with previously unpublished findings from a radiographic case series of patients treated with the Dewar procedure and a comparative group of patients treated with interspinous wiring or triple wiring fusion technique. The Dewar procedure served as an important evolutionary step toward our contemporary approach to fusion of the posterior column that minimizes tissue disruption and maximizes interfacet stabilization.